Aplicación de un procesador difuso tipo II en la ecualización de canales no lineales y variantes en el tiempo - Melgarejo Rey, Miguel Alberto; Peña Reyes, Carlos A. (Ingeniería, 2003)
This article describes an application context for a Type-2 fuzzy processor which has been implemented as a hardware solution. The processor is used to implement a fuzzy adaptive filter intended to perform a real-time equalization of a non-linear, time-variant communications channel. The fuzzy equalizer is characterized in terms of its Bit Error Rate and it is compared with a Type-1 fuzzy channel equalizer.Besides, it is observed experimentally how the resolution of the internal operations disturbs the performance of the equalizer. In this sense it is shown that a Type-2 fuzzy equalizer is more robust than a Type-1 when the resolution of their internal operations decreases.